A joint vessel for school effectiveness: school culture and climate - Koundyannan, Thiruchelvan; Abdul Kadir, Suhaida; Basri, Ramli; Mohd Ayub, Ahmad Fauzi (Faculty of Educational Studies, Universiti Putra Malaysia, 2019)
School culture and climate are two important elements in school management in improving school effectiveness. Both elements need parallel attention to ensure educational success. This study was conducted to examine the relationship and factors influencing effectiveness between School culture and climate at primary national schools (SK). The findings revealed, the correlation between School culture and climate dimensions. Three hundred fifty-three (353) teachers from 84 primary (SK) in Peninsular Malaysia participated in this study. Data were collected using the School Culture Survey (Gruenert, 1998, School Climate Instrument (Ross & Lowther, 2003) School Effectiveness Instrument (Lezotte dan Snyder, 2011). The analysis showed a significant correlation between School culture (M=4.15, SD=0.381) and School climate (M=4.13, SD = 0.310), r=.744, p=<0.01 in SK. The results of the Stepwise Multiple Regression analysis show that the School culture Regression Model P4 (Collaborative Leadership, Unity of Purpose, Learning Partnership and Teacher's Collaboration) contributed for 47.0% (R2=.470) changes in variance in School Effectiveness [F(4,348)=77.080, p<0.5]. The School climate regression model (Leadership, Instruction, Expectations and Environment) contributed 54.8% (R2=.548) of the variance in school effectiveness [F(4,348)=105.530, p<0.5]. The overall results of multiple regression analysis showed that the school culture Influence (β = .399, p<.05) compare than the school climate (β = .367, p<.05) with both combination significantly contributed 52.5% (R2= .525) of the variance change [F(2,350)=193.511, p<0.5]. In summary, finding showed a positive significant correlation between School culture and climate dimensions with p=<0.01, n=353. This model contributes to predicting the impact of school culture and climate on school effectiveness.